Israeli identity : in search of a successor to the pioneer, Tsabar, and settler - Weissbrod, Lilly, 1929- (Cass series--Israeli history, politics, and society., 2013)
This thoroughly researched book reveals the true identity of the modern Israeli. Israelis are unique in having changed their identity three times in only one hundred years. Written in a user-friendly style, the book will appeal to scholars and students of the Middle East.